A place to grow - Pak, Soyung; Truong, Marcellino (New York : A.A. Levine, 2002)
As a father tells his daughter what a seed needs to flourish, he also explains the reasons he emigrated to a new homeland.
Maps on endpapers.
3.6
K-3
Keywords: Fathers and daughters -- Fiction; Emigration and immigration -- Fiction; Gardening -- Fiction; Father-daughter relationship -- Fiction; Immigration and emigration -- Fiction; Gardening -- Fiction